Improving Student Learning Outcomes Through The Use of Powerpoint Media in PAI Learning in Class V SDN 09 Tarung Tarung Selatan - Siti Aisyah (BiCED Proceeding, 2024)
This study aimed to improve learning outcomes in Islamic Religious Education (PAI) for Grade V students at SDN 09 Tarung Tarung Selatan using PowerPoint media. The Classroom Action Research (CAR) method was conducted in two cycles, involving planning, implementation, observation, and reflection stages, with 16 student participants. Data were collected through formative tests, observations, and documentation and analyzed quantitatively and qualitatively. The results showed that using PowerPoint improved learning outcomes, with mastery reaching 75% in Cycle I and 100% in Cycle II. Challenges in student engagement were addressed by adding educational videos in Cycle II. Students better understood the material and applied moral values. It was concluded that PowerPoint is effective in enhancing PAI learning, offering engaging and relevant lessons. Teachers are encouraged to use this media creatively.